Amyloid Precursor Protein (APP) mediated regulation of ganglioside homeostasis linking alzheimer's disease pathology with ganglioside metabolism - Grimm, Marcus Otto Walter; Zinser, Eva G.; Grösgen, Sven; Müller, Ulrike C. (PLOS ONE, 2012)
Gangliosides are important players for controlling neuronal function and are directly involved in AD pathology. They are among the most potent stimulators of Aß production, are enriched in amyloid plaques and bind amyloid beta (Aß). However, the molecular mechanisms linking gangliosides with AD are unknown. Here we identified the previously unknown function of the amyloid precursor protein (APP), specifically its cleavage products Aß and the APP intracellular domain (AICD), of regulating GD3-synthase (GD3S). Since GD3S is the key enzyme converting a- to b-series gangliosides, it therefore plays a major role in controlling the levels of major brain gangliosides. This regulation occurs by two separate and additive mechanisms. The first mechanism directly targets the enzymatic activity of GD3S: Upon binding of Aß to the ganglioside GM3, the immediate substrate of the GD3S, enzymatic turnover of GM3 by GD3S was strongly reduced. The second mechanism targets GD3S expression. APP cleavage results, in addition to Aß release, in the release of AICD, a known candidate for gene transcriptional regulation. AICD strongly down regulated GD3S transcription and knock-in of an AICD deletion mutant of APP in vivo, or knock-down of Fe65 in neuroblastoma cells, was sufficient to abrogate normal GD3S functionality. Equally, knock-out of the presenilin genes, presenilin 1 and presenilin 2, essential for Aß and AICD production, or of APP itself, increased GD3S activity and expression and consequently resulted in a major shift of a- to b-series gangliosides. In addition to GD3S regulation by APP processing, gangliosides in turn altered APP cleavage. GM3 decreased, whereas the ganglioside GD3, the GD3S product, increased Aß production, resulting in a regulatory feedback cycle, directly linking ganglioside metabolism with APP processing and Aß generation. A central aspect of this homeostatic control is the reduction of GD3S activity via an Aß-GM3 complex and AICD-mediated repression of GD3S transcription.